2020
DOI: 10.1016/j.ajodo.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Control of SARS-CoV-2 transmission in orthodontic practice

Abstract: The coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has attracted worldwide concerns because of its high person-to-person infectivity and lethality, and it was labeled as a pandemic as the rapid increase in the number of confirmed patients in most areas around the world became evident. The SARS-CoV-2 is mainly transmitted through respiratory droplets and close contact. There is also evidence of transmission through aerosols and digestive tracts. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 38 publications
1
36
0
6
Order By: Relevance
“… Local sample survey 3 9 Eliades et al, 16 2020 To list the sources of aerosol production during an orthodontic standard procedure, analyze the constituent components of aerosol and their dependency on modes of grinding, the presence of water and type of bur, and suggest a method to minimize the quantity and detrimental characteristics of the particles comprising the solid matter of aerosol. Minimization Review of reported data 5 10 Guo et al, 17 2020 To update the preventive strategies for control of SARS-CoV-2 transmission to protect both staff and patients during the orthodontic practice. Narrative review 5 11 Turkistani K., 18 AJODO, 2020 To report to orthodontists on the emergence, epidemiology, risks, and precautions during the disease crisis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Local sample survey 3 9 Eliades et al, 16 2020 To list the sources of aerosol production during an orthodontic standard procedure, analyze the constituent components of aerosol and their dependency on modes of grinding, the presence of water and type of bur, and suggest a method to minimize the quantity and detrimental characteristics of the particles comprising the solid matter of aerosol. Minimization Review of reported data 5 10 Guo et al, 17 2020 To update the preventive strategies for control of SARS-CoV-2 transmission to protect both staff and patients during the orthodontic practice. Narrative review 5 11 Turkistani K., 18 AJODO, 2020 To report to orthodontists on the emergence, epidemiology, risks, and precautions during the disease crisis.…”
Section: Resultsmentioning
confidence: 99%
“… Studies providing guidelines and recommendations for orthodontic set-up and practice Studies mentioning appropriate appliance selection for an orthodontic practice. Isiekwe IG et al, 14 2020 Cotrin et al, 15 2020 Xiong Xi et al, 19 2020 Shenoi et al, 21 2020 Martina et al, 23 2020 Suri et al, 8 2020 Park et al, 9 2020 M. Srirengalakshmi et al, 10 2020 M. Srirengalakshmi et al, 11 2020 Perillo et al, 13 2020 Eliades et al, 16 2020 Guo et al, 17 2020 Turkistani K., 18 AJODO, 2020 Turkistani K., 20 2020 Garcia-Camba et al, 22 2020 Bennardo et al, 24 2020 M. Srirengalakshmi et al, 11 2020 Marya A., 12 2020 Perillo et al, 13 2020 Eliades et al, 16 2020 …”
Section: Resultsmentioning
confidence: 99%
“…The patients should be instructed to spit gently into a disposable cup. Use saliva ejectors with low or high volume to eject the gargle immediately to reduce the generation of droplets [40].…”
Section: Pre-procedural Mouthrinsesmentioning
confidence: 99%
“…For patients with high throat sensitivity, the reflector should not be placed too deep in the mouth, which may otherwise cause irritation, nausea, and vomiting, leading to the generation of droplets [41]. Photographers should strictly implement the principle of "one patient, one use, and one disinfection" for auxiliary equipment such as retractors and reflectors [40].…”
Section: Photographingmentioning
confidence: 99%
See 1 more Smart Citation